A qualitative study into the factors affecting final year nursing students’ confidence in practice - Allberry, Clare (2013)
Student nurses are expected to practice proficiently and confidently as they near the end of their course. This study examines the factors that affect this confidence in practice, and makes recommendations for practice changes to enhance future nursing students’ confidence. The study undertook semi-structured interviews with ten final year Master of Nursing Science (MNursSci) students from all three different specialities (paediatric [n=7], adult [n=2], mental health [n=1]). Analysis of the transcribed interviews found that the most important factors were time spent in university lectures (or ‘theory time’), the acquisition of new skills, mentorship, placements, and an ongoing transition of confidence. Recommendations for nursing practice include improvements to feedback for both mentors and students, and increased clinical skills during university time.